Savoirs naturalistes et stratégies de collecte de Geloina erosa, Geloina expansa et Polymesoda bengalensis dans la mangrove de l’île de Siberut (Indonésie) - Ariadna Burgos (Revue d'ethnoécologie)
The women from Katurai Bay (Siberut Island, Indonesia) explore the mangrove forest in search of crabs, fish and shellfish. Since their childhood, they have developed a close relationship with this environment and, with their experience have consolidated a corpus of ecological knowledge that allows them to assess the environment and optimize their day-to-day labor. Through an ethno ecological approach, the objective of this research was to examine the local knowledge and the techniques related to the collection of three big bivalves of the Cirenidae family. We have found that local knowledge is highly dynamic and combines multidisciplinary information - ecological, geographical and social – and key knowledge regarding the choice of the species and the place they are collected. But beyond their use as a key subsistence resource, mollusks are excellent bioindicators and provide a unique object to establish an interactive an complementary dialogue between scientists and local gatherers in the monitoring and assessment of coastal change.